People-, Process- and Goal-Focused Leadership Behaviour : an Empirical Study in a Global Company - Ha-Vikström, Thanh (University of Primorska, 2017)
This study explores the focus of leadership behaviours that perceived and experienced by leaders in a multinational company. By using triangulation method including questionnaires, in-depth interviews and observations, we analyse the data collected from twenty managers across organisational levels. The results reveal the patterns of managerial behaviour in three key focus areas for success: people, process and goal. Directors and general managers are more people-focused than line managers, who in turn tend to be more process-focused. The research findings bridge the gap in the field and initiate a new normative leadership behaviour model (people-, process and goal-focused), which can be used to directly support leaders in enhancing their leadership skills as well as for recruitment or promotion purposes. The model can be utilized as an aid to organisations when developing training programs to support leaders in different types of organisations (for-profit or non-profit) to focus their development efforts on organizational success.
Keywords: leadership behaviour; people-focused; process-focused; goal-focused